Calling the shots a queer history of photography - Clayton, Zorian; Caston, Lydia; Kaluznick, Hana (Thames & Hudson Ltd, 2024)
"An accessible, inspirational, and engaging introductory survey of LGBTQIA+ photography, as told through the collection of the Victoria and Albert Museum, London. Drawing on one of the oldest and largest photography collections in the world, Calling the Shots offers an unprecedented view of photographic history through a queer lens. It includes a broad range of global LGBTQIA+ representation from the mid-nineteenth century to now, presenting images from pioneering LGBTQIA+ photographers and subjects alongside work documenting activism and hard-won legal battles, over a century of performance, nightlife, and diverse queer communities, collectives, and subcultures. Following an introductory essay by Zorian Clayton, images are presented in six thematic chapters: Icons, Staged, Body, Liberty, Making a Scene, and Beyond the Frame. Each chapter opens with a short introductory essay, followed by an extended plate section. Expanded captions highlight key images, and "artist in focus" inserts draw on the work of selected photographers to illuminate particularly rich moments in LGBTQIA+ history. Bold proclamations of queer identity and community sit alongside personal explorations of self; documentation of struggle, joy, and everyday life is considered side-by-side with performances and photographic fictions that continue to challenge the bounds of gender and sexuality. This vital, accessible volume offers an exciting, expansive appraisal of photography's role in expressing, documenting, and celebrating queer life. It will be essential for all with an interest in the history of photography, but especially for those with an interest in LGBTQIA+ history" --
Keywords: Fotografie; LGBT -- Motiv; Geschlechtsidentität -- Motiv; Porträtfotografie; Victoria and Albert Museum; Photography, Artistic; Gay culture / Pictorial works; Gender-nonconforming people; Gender identity in art; Portrait photography; Gay people; Sexual minorities; Photographie artistique; Culture homosexuelle - Ouvrages illustrés; Identité de genre dans l'art; Portraits (Photographie); art photography; photobooks; Photobooks; Livres de photographies; Bildband